Faktor-Faktor Yang Mempengaruhi Efektivitas Penggunaan Aplikasi Sistem Keuangan Desa (Siskeudes) di Kecamatan Taman Kabupaten Sidoarjo - Preswari, Raksi; Ratnawati, Dyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to determine the influence of the quality of human resources, education & training, the role of village assistants, and community participation on the effectiveness of using the village financial system application (Siskeudes) in Taman District, Sidoarjo Regency. The sample in this study was 80 village officials in Taman District. The analysis technique used in this research is a multiple linear analysis technique. The research results show that first, the quality of human resources has a positive effect on the effectiveness of using the village financial system application (Siskeudes). Second, education & training has a positive effect on the effectiveness of using village financial system applications (Siskeudes). Third, the role of village assistants does not have a positive effect on the effectiveness of using village financial system applications (Siskeudes). Fourth, community participation does not have a positive effect on the effectiveness of using the village financial system application (Siskeudes).